Humoristes cherchent « safe spaces » - Blais-Poulin, Charles-Éric (La Presse, 2022)
Harcèlement en ligne, blagues sexistes, sous-représentation féminine, culture du silence : des humoristes n’entendent plus à rire. Elles sont « fucking tannées », « exténuées », « fâchées ». Et certaines aménagent leurs propres « safe spaces » (espaces sûrs), si de tels lieux existent.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; LGBTQIA2+; amériques; approches et analyses; dénonciations en ligne; identités LGBTQIA2+; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; safe space; sororité; systèmes d'oppressions; thématiques; travail; violences; violences sexistes et sexuelles

La Minotaure - Maréchal, Maël (Queer, 2019)
La Minotaure est un roman dans lequel une narratrice particulièrement terrifiée par l'idée de vivre témoigne de son enfance à travers des notes pour comprendre la source de ses effrois. La plupart de ses courts textes sont adressées à Maude, une amie décédée. Ce (faux) dialogue lui permet de tisser des liens entre son enfance et son âge adulte, et entre sa vie et sa mort qui, croit-elle, la guette à cause de cette tentation d'exister. C'est le récit d'une parole qui ose s'affirmer, d'une personne qui décide enfin d'exister à travers un noeud de violence patriarcale, blanche, impérialiste, de genre et de classe sociale qui l'étouffe, la transperce et l'invisibilise. C'est surtout l'histoire d'un millier de miroirs qui brisent sous une terrible impulsion à vivre.
Keywords: LGBTQIA2+; amériques; approches et analyses; arts; canada; classisme; cours; discipline; genre; histoire et politique; identité; identités LGBTQIA2+; lit3220; patriarcat; premier cycle; queer; québec; racisme; roman; régions géographiques; systèmes d'oppressions; thématiques; violences; écriture des femmes*; études littéraires

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Dude, you're a fag: masculinity and sexuality in high school : with a new preface - Pascoe, C. J. (University of California Press, 2012)
"High school and the difficult terrain of sexuality and gender identity are brilliantly explored in this smart, incisive ethnography. Based on eighteen months of fieldwork in a racially diverse working-class high school, Dude, You're a Fag sheds new light on masculinity both as a field of meaning and as a set of social practices. C.J. Pascoe's unorthodox approach analyzes masculinity as not only a gendered process but also a sexual one. She demonstrates how the 'specter of the fag' becomes a disciplinary mechanism for regulating heterosexual as well as homosexual boys and how the 'fag discourse' is as much tied to gender as it is to sexuality"--Provided by publisher.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; adolescents*; amériques; approches et analyses; californie; cours; discipline; ethnographie; hétérosexisme; masculinité; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

La fille qui rêvait d'embrasser Bonnie Parker - Gagnon, Isabelle (Les éditions du remue-ménage, 2010)
Florence, 16 ans, vit avec son père, sa mère et Thomas, son frère de 14 ans, avec qui elle se chamaille tout le temps. Elle ne s'entend guère mieux avec sa mère. Florence n'est pas une fille très sociable. Elle trouve sa vie d'un ennui mortel, n'a pas beaucoup de copines ni d'amoureux. Par contre, elle a un ami fidèle, le beau Andy, qu'elle considère comme un frère; et avec qui elle joue de la guitare électrique. Ils projettent de former un groupe musical, sous le nom de Bonnie and Clyde. Florence fréquente l'école secondaire. Bref, le quotidien banal de beaucoup d'adolescent.e.s. Mais pourquoi se sent-elle parfois tellement à part? Différente des autres jeunes de son âge dans ses goûts, ses intérêts, ses rêves. Pourquoi est-elle si bouleversée par le retour en ville de Raphaëlle, son amie d'enfance? La venue de son amie oblige Florence à se questionner sur elle-même. Son attirance pour Raphaële est-elle normale? Ses questionnements et l'arrivée de Raphaëlle qui lui révèle son homosexualité, oblige Florence à jeter le masque : elle est lesbienne, elle préfère les filles aux garçons. Une prise de conscience douloureuse, car révéler son homosexualité n'est jamais facile. Florence devra faire face aux autres jeunes, à sa famille et à la société.Un récit très pudique qui parle d'un sujet souvent inexploité en littérature jeunesse : l'amour homosexuel entre filles. L'intrigue aborde aussi le questionnement identitaire, la difficulté de s'accepter, de se faire accepter, en plus d'ajouter une note plus sombre au portrait : l'homophobie. À cause de sa différence, Florence est invectivée de façon grossière et son frère se fera tabasser pour l'avoir défendue. Mais, s'il faut beaucoup de courage pour garder la tête haute, les mentalités ont heureusement évolué. Un roman qui veut démystifier l'homosexualité et permettre aux adolescent.e.s homosexuel.les de s'accepter. En annexe : un guide de ressources et d'aide aux jeunes.
Keywords: adolescence; amitié; amériques; approches et analyses; homophobie; hétérosexisme; identités LGBTQIA2+; patriarcat; personnes lesbiennes; québec; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences

Le sexe du militantisme - Fillieule, Olivier; Roux, Patricia (Presses de Sciences Po, 2009)
Le sexe du militantisme propose une analyse de la (re)production des rapports de pouvoir au travers des pratiques militantes, saisissant les logiques par lesquelles les inégalités de genre, de classe et de race imprègnent le militantisme, qu'il soit de gauche ou de droite, progressiste ou conservateur. Premier ouvrage en français à explorer le militantisme dans une perspective de genre à partir de recherches empiriques sur les partis, les syndicats et les mouvements sociaux, il rassemble des politistes, sociologues, anthropologues et historiennes dont le souci est de ne pas appréhender les luttes politiques comme si elles étaient « neutres » et non sexuées. Une contribution majeure à l'étude des mobilisations collectives qui complète les analyses classiques, aveugles aux rapports de genre.
Keywords: LGBTQIA2+; amérique du nord; amérique latine; amériques; anarchisme; anthropologie; approches et analyses; asie; canada; caraïbes; discipline; europe; france; genre; guyane française; histoire; hétérosexisme; identités LGBTQIA2+; inégalités; israël; italie; militance; mouvements sociaux; patriarcat; québec; racisme; rapports sociaux; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; syndicat; système colonial; systèmes d'oppressions; thématiques; violences

Thinking straight: the power, the promise, and the paradox of heterosexuality - Ingraham, Chrys (Routledge, 2005)
This collection of original essays will unravel the current heterosexual scene in two parts: one on rights and privileges, the other on popular culture. Topics covered include weddings, proms, citizenship, marriage penalties, cartoons, mermaids and myth.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; hétéronormativité; hétérosexisme; hétérosexualité; mariage; patriarcat; premier cycle; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Femmes et égalité - Institut de recherches et d'études féministes (FéminÉtudes, 2005)
Cette publication porte sur la place et la notion d’égalités dans les luttes féministes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; antiféminisme; approches et analyses; care; droits des femmes*; féminétudes; genre; identités LGBTQIA2+; patriarcat; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; égalité femme*-homme

Make Room for Daddy: Anxious Masculinity and Emergent Homophobias in Neopatriarchal Politics - Stein, Arlene (Gender and Society, 2005)
What are the sources of continuing antipathy toward homosexuality, and what might they tell us about changing forms of American masculinity? This article documents some emergent homophobias circulating among conservative activists in relation to campaigns against gay rights in the early 1990s and against gay marriage in 2004. As feminist critiques of traditional masculinity make their way into conservative rhetoric and as men struggle to define a role that maintains male authority without sounding overly authoritarian, new forms of homophobia have emerged that are compatible with conservatives' quest to be seen as compassionate protectors of the family.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; homophobie; hétérosexisme; masculinité; militance; patriarcat; premier cycle; périodes; périodes historiques; régions géographiques; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; états-unis

Les familles homosexuelles aux États-Unis : dissolution d'un mouvement social ou redéfinition de sa portée politique? - Marche, Guillaume (Revue française d'études américaines, 2003)
Families are a challenge to the lesbian and gay movement in the United States, since homosexuality is largely construed as antithetical to "the family". By creating a wide variety of alternative families gays and lesbians however articulate an identity claim which may not be framed exclusively either in terms of assimilationism, or of differentialism. For this reason these alternative families present American society with a transformative potential which is in a position to exert its influence beyond the bounds of the gay and lesbian community. Far from being a hindrance in terms of efficiency, the very fact that these families constitute a private locus of gay and lesbian experience furthermore contributes to the lesbian and gay movement's expressive dimension, which is of crucial strategic importance in contemporary American society.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; famille; familles homoparentales; his4443; homoparentalité; hétérosexisme; identités LGBTQIA2+; lesbianisme; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; parentalité; patriarcat; philosophie politique; premier cycle; queer; régions géographiques; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques; états-unis; études américaines

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Between men--between women, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques